Analisa Konseptual Tentang Karunia Mengajar - Sunarti, Sunarti; Yanti, Naomi Anggrawita (Jurnal Kala Nea, 2021)
God equips teachers with the power and wisdom of the Holy Spirit, even so God still wants every teacher to have a mature readiness to become God’s tool in the world of education. This study aims to find out the problems that occur why Sunday school children at the Tegal Bethel Maranatha Chrurch in Central Tegal find it very difficult to concentrate when their teacher is explaining and the results of this study are finding the empowerment of the gift of teaching in the Sunday School teacher ministry according to Romans 12:6-8 in Tegal Center Bethel Maranatha Church is low due to several factors listed in this study.